The Relationship between Breastfeeding Education Classes and Breastfeeding for Infants at the Benteng Public Health Center, Nusaniwe District, Ambon City - Algraciela Pellaupessy; Regina Vidya Trias Novita (Universitas Muhammadiyah Surakarta, 2023)
Breastfeeding is an activity of providing nutrition for newborns which requires of skills, so they need of accompaniment from health workes to achieve first thousand days of life periode (kemenkes,2016). Based on World Health Organization (2016) fluctuation of exclusive breastfeeding still very far from target of 80%. The purpose of this study to find out about relationship between breastfeeding education classes with mother with toddler breastfeeding at the Benteng health center, Nusaniwe, Ambon City. Correlative descriptive reasearch method with approach cross sectional. The sampling technique use purposive sampling as many as 260 mother who had toddlers. The research sample is mother who had toddler with a sample of 158 respondent. Data collection tools is used form of questionnaire. Data analysis was carried out using chi square test with trusted level a = 0,05. The result of this study were obtained about education classes of Antenal Care most result are who follow education classes (79,1%). Post partum education classes most result are who follow education classes (68,4%). Result for breastfeeding 6 months are (84,8%), result for breastfeeding >6month-1years are (79,7%) and result for breastfeeding >1-2years are (53,8%). The result statistics of Chi Square test showed a significant relationship between Antenal Care education classes with breastfeeding for 6 months (p value 0.012), then there is a significant relationship between Anetal Care education classes with breastfeeding >6month-1years (p value 0.035), nothing relationship between Anetal Care education classes with breastfeeding >1-2years (p value 0.328), nothing relationship between Post Partum education classes with breastfeeding 6 months (p value 0.340), Post partum education classes with breastfeeding >6month-1years (p value 0.832), and Post Partum education classes with breastfeeding >1-2years (p value 1.000).